Composition dependent phase structure, dielectric and electrostrain properties in (Sr0.7Bi0.2□0.1)TiO3–PbTiO3–Bi(Mg0.5Ti0.5)O3 systems. (5th May 2022) - Shi, Hongwei; Li, Feng; Liu, Wei; Liang, Cen; Ji, Xiaoli; Long, Mingsheng; Gong, Weiping; Wang, Chunchang; Shan, Lei
Abstract: Composition dependent transitions from normal ferroelectrics to nonergodic and finally to ergodic relaxor phase are observed in 0.7(Sr0.7 Bi0.2 □0.1 )TiO3 –(0.3 − x )PbTiO3 – x Bi(Mg0.5 Ti0.5 )O3 system (SBT–PT– x BMT, □ represents A–site vacancy). Rietveld refinement results show that with increasing BMT content, the system experiences a gradual transition from coexistence of pseudocubic and tetragonal ( P c + T ) to P c phase. The ferroelectric–relaxor phase transition and freezing temperature gradually decreases with addition of BMT content accompanied by an enhanced relaxor degree, which produces local disorder and polar nanodomains. This is also verified by Raman spectra and piezoelectric force microscopic analysis. The P – E loops transform from square to slant and finally to slim shape with increasing BMT component and an electric field-induced strain of ∼0.21% with ultralow hysteresis of ∼3.7% is obtained for x = 0.04 composition. The underlying mechanism for the large strain with low hysteresis lies in the existence of nonergodic and ergodic relaxor phase boundary and polar nanodomains at room temperature. Additionally, the multiphase coexistence contributes to a flatten free energy profile and thus contributing to such superior performances, as explained by a modified phenomenological model. High electrostrain with ultralow hysteresis in SBT–PT– x BMT systems are promising candidates in high–precision actuator applications.